External validation of blue light imaging (BLI) criteria for the optical characterization of colorectal polyps by endoscopy experts. Issue 10 (6th May 2021) - Desai, Madhav; Kennedy, Kevin; Aihara, Hiroyuki; Van Dam, Jacques; Gross, Seth; Haber, Gregory; Pohl, Heiko; Rex, Douglas; Saltzman, John; Sethi, Amrita; Waxman, Irving; Wang, Kenneth; et al.
Abstract: Background and Aim: Recently, the BLI Adenoma Serrated International Classification (BASIC) system was developed by European experts to differentiate colorectal polyps. Our aim was to validate the BASIC classification system among the US‐based endoscopy experts. Methods: Participants utilized a web‐based interactive learning system where the group was asked to characterize polyps using the BASIC criteria: polyp surface (presence of mucus, regular/irregular and [pseudo]depressed), pit appearance (featureless, round/non‐round with/without dark spots; homogeneous/heterogeneous distribution with/without focal loss), and vessels (present/absent, lacy, peri‐cryptal, irregular). The final testing consisted of reviewing BLI images/videos to determine whether the criteria accurately predicted the histology results. Confidence in adenoma identification (rated "1" to "5") and agreement in polyp (adenoma vs non‐adenoma) identification and characterization per BASIC criteria were derived. Strength of interobserver agreement with kappa (k) value was reported for adenoma identification. Results: Ten endoscopy experts from the United States identified conventional adenoma ( vs non‐adenoma) with 94.4% accuracy, 95.0% sensitivity, 93.8% specificity, 93.8% positive predictive value, and 94.9% negative predictive value using BASIC criteria. Overall strength of interobserver agreement was high: kappa 0.89 (0.82–0.96). Agreement for the individual criteria was as follows: surface mucus (93.8%), regularity (65.6%), type of pit (40.6%), pit visibility (66.9%), pit distribution (57%), vessel visibility (73%), and being lacy (46%) and peri‐cryptal (61%). The confidence in diagnosis was rated at high ≥4 in 67% of the cases. Conclusions: A group of US‐based endoscopy experts have validated a simple and easily reproducible BLI classification system to characterize colorectal polyps with >90% accuracy and a high level of interobserver agreement.